2015
DOI: 10.1016/j.brat.2015.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Can adaptive treatment improve outcomes in family-based therapy for adolescents with anorexia nervosa? Feasibility and treatment effects of a multi-site treatment study

Abstract: Objective Adolescents with Anorexia Nervosa (AN), treated with family-based treatment (FBT) who fail to gain 2.3 kg by the fourth week of treatment have a 40–50% lower chance of recovery than those who do. Because of the high risk of developing enduring AN, improving outcomes in this group of poor responders is essential. This study examines the feasibility and effects of a novel adaptive treatment (i.e., Intensive Parental Coaching-IPC) aimed at enhancing parental self-efficacy related to re-feeding skills in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
114
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 121 publications
(117 citation statements)
references
References 33 publications
1
114
0
2
Order By: Relevance
“…An important focus of FBT is helping parents understand that patients restrict their food intake because they are in the grip of a powerful disorder that is causing them to be fearful of food and weight gain. Lock et al (2015) have shown that intensified treatment improves outcome for families identified as at risk for poor outcomes based on lack of early weight gain. Interventions specifically to reduce expressed emotion in eating disorders have been shown to improve patient outcome (Hibbs et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…An important focus of FBT is helping parents understand that patients restrict their food intake because they are in the grip of a powerful disorder that is causing them to be fearful of food and weight gain. Lock et al (2015) have shown that intensified treatment improves outcome for families identified as at risk for poor outcomes based on lack of early weight gain. Interventions specifically to reduce expressed emotion in eating disorders have been shown to improve patient outcome (Hibbs et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Future studies might consider utilizing CBT-E, adapted for adolescents, as this approach is the latest iteration of CBT for eating disorders now available. Alternatively, the utility of integrative cognitive-affective therapy 41 or interpersonal therapy, 6 if adapted for adolescents, or a stepped-care approach for early non-responders, 42 could also be explored. Finally, this is only the third, though largest, RCT conducted to examine treatments for adolescents with BN.…”
Section: Discussionmentioning
confidence: 99%
“…These include Enhancing parents’ self-efficacy through intensive parent coaching alongside FBT23 or through groups’ teaching communication skills, motivational interviewing and meal support to parents and carers 24

Providing therapy to parents alone using an FBT format (separated FBT) if levels of criticism and conflict are high in conjoint therapy 25

…”
Section: Anorexia Nervosamentioning
confidence: 99%
“…Enhancing parents’ self-efficacy through intensive parent coaching alongside FBT23 or through groups’ teaching communication skills, motivational interviewing and meal support to parents and carers 24…”
Section: Anorexia Nervosamentioning
confidence: 99%